Transition, not revolution - Popov, Mikhail; Heidrich, Claudia; Shore, Andrew (Septentrio Conference Series, 2018)
Watch the VIDEO. This presentation is aiming to discuss the effects of conversion of a journal to OA and suggests that this is likely to cause a loss of authorship of the journal. Further, we conclude that transitioning to OA via hybrid models is a more sustainable approach than flipping all journals to OA at once. As an example we use RSC Advances – a high quality journal in multidisciplinary chemistry published by RSC. Since launch in 2012, RSC Advances has achieved rapid growth and worldwide acceptance. In 2016 we converted RSC Advances to OA to: • give researchers free access to a broad scope of quality work • make the research we publish more visible • positively influence the future of OA publishing • demonstrate that OA publishing can be both affordable, and sustainable An anticipated result of flipping to open access is the loss of authorship and submissions to competing journals. In fact, in 2017 just over 6600 articles were published in RSC Advances – less than a half of the publishing output in 2016. The loss of authorship and a risk of authors choosing to publish in a competing journal is the reason why RSC cannot go full OA (all journals) yet. This does not mean that RSC suspended the support of OA. We continue introducing new OA journals like Nanoscale Advances, and new OA transition models like Read & Publish, which allows authors to access all content behind paywall and publish OA at no extra cost.